2022
DOI: 10.1302/0301-620x.104b5.bjj-2021-1706.r2
|View full text |Cite
|
Sign up to set email alerts
|

Additional operations after surgery for lumbar disc prolapse

Abstract: Aims Lumbar disc prolapse is a frequent indication for surgery. The few available long-term follow-up studies focus mainly on repeated surgery for recurrent disease. The aim of this study was to analyze all reasons for additional surgery for patients operated on for a primary lumbar disc prolapse. Methods We retrieved data from the Swedish spine register about 3,291 patients who underwent primary surgery for a lumbar disc prolapse between January 2007 and December 2008. These patients were followed until Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This association between previous operations and inferior outcomes confirm the findings in previous but smaller studies, including one previous data analysis from NORspine. [3][4][5][6][7][8][9] Only the register-based studies by Zehnder et al 6 and Sigmundsson et al 9 categorized participants based on the number of previous operations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This association between previous operations and inferior outcomes confirm the findings in previous but smaller studies, including one previous data analysis from NORspine. [3][4][5][6][7][8][9] Only the register-based studies by Zehnder et al 6 and Sigmundsson et al 9 categorized participants based on the number of previous operations.…”
Section: Discussionmentioning
confidence: 99%
“…Sigmundsson et al 9 analyzed 681 (21%) additional operations after 3,291 primary operations, and reported a stepwise decrease in change scores for NRS leg pain from 5.5 among cases with no previous operations to 1.2 among cases with three previous operations. 9 The corresponding figures in the present study were 4.0 and 2.5. There were similar corresponding observations between the studies for NRS back pain and EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spondylolisthesis [7] and decompression-induced iatrogenic instability [8] have been recognized has indications for lumbar spinal fusion. Endoscopic decompression surgery is increasingly being used as a less burdensome and simplified alternative to more traditional, open, and minimally invasive decompression techniques [9]. While a formal prospective cohort study is currently underway comparing lumbar endoscopic decompression to open decompression and fusion [10], existing studies suggest that lumbar endoscopic stenosis decompression in the central and lateral canal is associated with a low long-term fusion rate, with one study identifying a rate of 2.7% [11] and another, 8.9% [12].…”
Section: Introductionmentioning
confidence: 99%